DEVELOPING PPT INTERACTIVE TO TEACH SPEAKING SKILL IN RECOUNT TEXT MATERIAL - M. Misbakhul Zaki Munir; Istina Atul Makrifah; Ahmad Saifudin (PROJECT (Professional Journal of English Education), 2023)
This research aims to develop PPT interactive English for recount text material at MA Ma'arif Udanawu. This product was developed in response to the dearth of teaching resources available to educators. Since textbooks and ebooks are typically the only learning tools used, the offered information is less engaging. Students also lack self-assurance when speaking. They fear making grammatical or pronunciation errors. The aim of this research is to create an ADDIE-based PPT interactive. Interviews and questionnaires were used to gather data. At MA Ma'arif Udanawu, 38 students in MIPA 5 received questionnaires. In the meantime, the English teacher and several students were interviewed. The validity of PPT interactive learning media on English material with recount text material has been tested with the results of instrument validity of 88%, media (design) validity of 100% and material validity (content) of 97% with very valid criteria and feasible to use. The practicality of interactive PPT learning media on recount text material obtained a questionnaire result from student responses of 82% with very practical and appropriate criteria for use.